2022
DOI: 10.3389/fmicb.2022.844283
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Plasma Reveals Differential Disease Severity Markers in COVID-19 Patients

Abstract: The severity, disabilities, and lethality caused by the coronavirus 2019 (COVID-19) disease have dumbfounded the entire world on an unprecedented scale. The multifactorial aspect of the infection has generated interest in understanding the clinical history of COVID-19, particularly the classification of severity and early prediction on prognosis. Metabolomics is a powerful tool for identifying metabolite signatures when profiling parasitic, metabolic, and microbial diseases. This study undertook a metabolomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 85 publications
(99 reference statements)
0
16
0
Order By: Relevance
“…Recent literature reported altered amino acid and lipid precursors in plasma from COVID-19 patients, with metabolite levels correlating with disease severity and risk of hospitalization, suggesting that the implementation of a KD may improve patient health. 50,51,59,60,[67][68][69][70][71][72][73][74][75] However, robust followup clinical studies are needed to translate these findings into clinical recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature reported altered amino acid and lipid precursors in plasma from COVID-19 patients, with metabolite levels correlating with disease severity and risk of hospitalization, suggesting that the implementation of a KD may improve patient health. 50,51,59,60,[67][68][69][70][71][72][73][74][75] However, robust followup clinical studies are needed to translate these findings into clinical recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…All these contributions highlight the critical role that kynerurate pathway has in the metabotype associated to the disease severity ( D’Amora et al, 2021 ; Marín-Corral et al, 2021 ; Roberts et al, 2022 ). Dysregulated amino acids ( Ibarra-gonza et al, 2022 ), alterations in intermediates of amino acid catabolism ( Páez-Franco et al, 2021 ) and elevated porphyrins ( San Juan et al, 2020 ; Oliveira et al, 2022 ) are also linked to severe phenotypes of the disease.…”
Section: Biomarkers Of Covid-19 Severitymentioning
confidence: 99%
“…Particularly, altered energy metabolism and hepatic dysfunction are brought on by malic acid of the TCA cycle as well as the carbamoyl phosphate of the urea cycle [ 176 ]. Another metabolomic pathway analysis revealed that the individuals affected with COVID-19 were found to have an impact on glycerophospholipid and the porphyrin metabolism but at the same time showed a significant effect on the glycerophospholipid and linoleic acid metabolism pathways [ 177 ]. Shen et al, analyzed the proteome and metabolome of the sera from several COVID-19 patients by applying proteomics and metabolomics to test whether any characteristic molecular changes are induced by SARS-CoV-2.…”
Section: Metabolomics Covid-19 and Kidney Injurymentioning
confidence: 99%